The child penalty in Sweden: Evidence, trends, and child gender - Anton Sundberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
This paper examines the impact of parenthood on labor market outcomes for both men and women using population-wide annual income data from 1960 to 2021 in Sweden. First, I document the contemporary child penalties across several labor market outcomes. Second, I show that while the motherhood penalty in earnings declined significantly during the 1960s, 1970s, and early 1980s, the rate of decline slowed from the late 1980s onwards. Third, I identify a fatherhood penalty emerging since the 1980s, particularly pronounced among men in more gender-egalitarian households (proxied by the father's share of parental leave) and among fathers who have sons relative to daughters.
Keywords: J13; J16; J22; J31; 330; Parenthood; child penalties; gender earnings gap